How many genes can make a cell: the minimal-gene-set concept. - Koonin, E V (Annu Rev Genomics Hum Genet, 2000)
Several theoretical and experimental studies have endeavored to derive the minimal set of genes that are necessary and sufficient to sustain a functioning cell under ideal conditions, that is, in the presence of unlimited amounts of all essential nutrients and in the absence of any adverse factors, including competition. A comparison of the first two completed bacterial genomes, those of the parasites Haemophilus influenzae and Mycoplasma genitalium, produced a version of the minimal gene set consisting of approximately 250 genes. Very similar estimates were obtained by analyzing viable gene knockouts in Bacillus subtilis, M. genitalium, and Mycoplasma pneumoniae. With the accumulation and comparison of multiple complete genome sequences, it became clear that only approximately 80 genes of the 250 in the original minimal gene set are represented by orthologs in all life forms. For approximately 15% of the genes from the minimal gene set, viable knockouts were obtained in M. genitalium; unexpectedly, these included even some of the universal genes. Thus, some of the genes that were included in the first version of the minimal gene set, based on a limited genome comparison, could be, in fact, dispensable. The majority of these genes, however, are likely to encode essential functions but, in the course of evolution, are subject to nonorthologous gene displacement, that is, recruitment of unrelated or distantly related proteins for the same function. Further theoretical and experimental studies within the framework of the minimal-gene-set concept and the ultimate construction of a minimal genome are expected to advance our understanding of the basic principles of cell functioning by systematically detecting nonorthologous gene displacement and deciphering the roles of essential but functionally uncharacterized genes.